Efektivitas Perbandingan Obat Seftriakson dan Sefotaksim pada Pasien Demam Tifoid Rawat Inap RSD X Kota Cirebon Tahun 2023 - Like Efriani; Teguh Adiyas Putra; Euis Nurkholifah Mahendra (Dinasti Research, 2024)
Typhoid fever is a gastrointestinal infection caused by Salmonella typhi, with significant prevalence in Indonesia. This study aims to compare the effectiveness of using ceftriaxone and cefotaxime antibiotics in hospitalized patients with typhoid fever at Hospital X in Cirebon City. The research method employed was a non-experimental observational study with a retrospective cross-sectional design, utilizing patient medical records from January to December 2023. The study results indicate that ceftriaxone was more frequently prescribed than cefotaxime (69% vs. 31%) at Hospital X. Regarding the reduction of body temperature, ceftriaxone demonstrated higher effectiveness compared to cefotaxime, although there was no significant difference in length of hospital stay between the two treatments. Ceftriaxone was also more effective in returning leukocyte counts to normal compared to cefotaxime. Based on these findings, ceftriaxone remains the preferred choice for treating typhoid fever at Hospital X in Cirebon City due to its superior effectiveness in reducing body temperature and restoring leukocyte counts to normal. These results can serve as important references for clinical decision-making regarding typhoid fever treatment in the future.